Synthesis and in-vitro toxicity evaluation of anticancer drugs-loaded chitosan nanoparticles as therapeutic nanocarriers for the treatment of hepatocellular carcinoma - Mohammed, Albalawi Fahad (2023)
Hepatocellular carcinoma (HCC) is among the most common liver cancers globally with more than 600,000 new patients diagnosed annually. The limitations of chemotherapy in treating HCC include poor aqueous solubility, nonspecific targeting of anticancer drugs, low retention of drugs in the tumor, and multi-drug resistance. The development of innovative intervention tools for early diagnosis and treatment has gained exceptional interest in HCC management. However, HCC is a multifactorial disease that requires a combination of treatment plans rather than a single therapeutic agent targeting only a single target. The complication of the disease, such as liver cirrhosis, limits surgical and therapeutic options due to liver malfunction might result in alteration of the safety profiles of systemic agents. Thus, multi-target inhibitors (MTIs) and multi-drug inhibitors (MDIs) that combine several drugs to inhibit numerous pathways are vital in treating HCC, but they may induce systemic toxicity due to liver malfunction. The concept of employing nanoparticles (NPs) in delivering multitarget inhibitors (MTIs) and multi-drug inhibitors (MDIs) has a strong potential in the therapeutic strategy and offers impressive outcomes to address HCC. Chitosan nanoparticles (ChNPs) have a great potential to be used as a drug delivery system in HCC therapy over conventional drug therapy. Furthermore, the anti-HCC drug-loaded ChNPs can lessen the dosage amount and duration of treatment and could resolve the problems of low and poor compliance, therefore, significantly reducing the side effects. In this work, encapsulated, single-loaded, and dual-loaded FDA-approved anti-HCC drugs (small molecule kinase inhibitors); cabozantinib (CBZ) and sorafenib (SF), and the antimetabolite drug, 5-fluorouracil (5FU) into chitosan NPs, were synthesized for better efficacy on HCC treatment with fewer drug side effects. These novel nanocarriers enhanced effective permeation through the cells, better stability in the bloodstream, and demonstrated controlled release capability of the encapsulated drugs, resulting in more potent multitarget inhibitors for HCC treatment. In this study, the ionic gelation technique was used to synthesize chitosan NPs, loaded with MTIs and MDIs, via a crosslinking agent, sodium tripolyphosphate (TPP) with various Ch to TPP ratios (1:1.25, 1:2.5, 1:5, 1:10, 1:20). Subsequently, the impact of the amount of TPP on the reaction yield, particle size, entrapment efficiency, anticancer activities, and in-vitro drug release was explored. The increase in the TPP concentration led to a smaller particle size. The chitosan nanocarriers were found to be uniform in size with high drug loading and encapsulation efficiency. At the ratio of 1:2.5, ChNPs with single-loaded MTI were found to be in the range of 100 nm in their mean particle size distribution (PSD), compared to around 50 nm for dual drug-loaded ChNPs. The encapsulation efficiencies for single-loaded drugs are in the range of 40- 50% compared to 50-70% for the dual-loaded. The XRD and FTIR of chitosan nanoparticles revealed an amorphous nature, which confirmed that the crystal structure of the drug was tapered. All the drugs from all the nanocarriers systems underwent a sustained release as evident in the in-vitro release study, as indicated by the TGA/DTG thermograms. Overall, the majority of the drugs show 90-100% release within the first 120 hours for all the samples. The cytotoxicity of these synthesized nanodelivery systems was evaluated by In Vitro study using normal human dermal fibroblast adult cells (HDFa) cells and human liver hepatocellular carcinoma (HepG2) cell lines. The nanocarriers system for the MTIs and MDIs showed low toxicity to the normal humandermal fibroblast adult cells (HDFa). The single- and dual-loaded drug systems exhibited anticancer effects, which were better achieved with MDIs compared to MTIs. Conclusively, CS/TPP concentration is one of the most important factors in optimizing the formulation for the development of anti-HCC nanocarriers. Dual drug-loaded CSNP systems are a novel and promising approach to enhancing therapeutic efficacy and reducing the deleterious effects of MDIs and MTIs. Findings from this work could lead to a new generation of nanodrug delivery systems of tailormade multifunctional properties with better efficacy and accuracy.